2011
DOI: 10.1371/journal.pone.0019139
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 Induced Angiogenesis through AKT and ERK Activation and HIF-1α Expression

Abstract: MicroRNAs (miRNAs) are endogenous, small noncoding RNAs that play important roles in various cellular functions and tumor development. Recent studies have indicated that miR-21 is one of the important miRNAs associated with tumor growth and metastasis, but the role and molecular mechanism of miR-21 in regulating tumor angiogenesis remain to be elucidated. In this study, miR-21 was overexpressed by transfecting pre-miR-21 into human prostate cancer cells and tumor angiogenesis was assayed using chicken chorioal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
353
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(383 citation statements)
references
References 48 publications
27
353
0
3
Order By: Relevance
“…This is not surprising, as several of the key molecular regulators of angiogenesis, such as VEGFs, are also common to lymphangiogenesis during inflammation (1). miR-21, which has been shown to be both anti-and proangiogenic (33,52), is significantly upregulated in LECs in response to TNF-␣ ( Table 1). Results of the latter study (52) are consistent with our findings that miR-21 mimics reduced tube formation in LECs (Fig.…”
Section: Mir-21 and The Mir-17-92 Clustermentioning
confidence: 99%
“…This is not surprising, as several of the key molecular regulators of angiogenesis, such as VEGFs, are also common to lymphangiogenesis during inflammation (1). miR-21, which has been shown to be both anti-and proangiogenic (33,52), is significantly upregulated in LECs in response to TNF-␣ ( Table 1). Results of the latter study (52) are consistent with our findings that miR-21 mimics reduced tube formation in LECs (Fig.…”
Section: Mir-21 and The Mir-17-92 Clustermentioning
confidence: 99%
“…This observation unveils a novel pathway Both AKT and ERK are downstream regulators of the miR-21/PTEN pathway. 46 It is also known that ENaC activity is regulated by a complex network of signaling pathways in addition to the AKT and ERK pathways. 50 We previously demonstrated that the AKT pathway mediated the LPSinduced decrease of cystic fibrosis transmembrane conductance regulator protein expression in primary ATII cells.…”
Section: Discussionmentioning
confidence: 99%
“…46 Therefore, we examined whether these signaling pathways were involved in the regulation of ENaC-γ protein expression after LPS treatment. First, we examined the phosphorylation of AKT and ERK in LPS-stimulated A549 cells.…”
Section: Lps Decreased Enac-γ Protein Expression In a Mir-21/ Pten Akmentioning
confidence: 99%
“…Many of the bovine miRNAs differentially expressed in large atretic follicles are reportedly involved in regulating the proliferation and survival of different cell types (miR-483, miR-150, miR-21, miR-409a, miR-31, miR-34b, miR-33a; Yamakuchi et al 2008, Bertero et al 2011, Liu et al 2011, Brabletz 2012, Cirera-Salinas et al 2012, Weng et al 2012 as well as immune cell activation (miR-150, miR-21, miR-31; Xiao et al 2007, Xue et al 2013, Das et al 2014, which is consistent with an active role of these miRNAs in follicular fate decisions. The involvement of miR-21 in the promotion of cell survival is well established, including in mouse granulosa cells during ovulation (Carletti et al 2010).…”
Section: Discussionmentioning
confidence: 99%